Diagnosis and surgical outcomes of ectopic ureters in adults: A case series and literature review. Issue 6 (3rd June 2019) - Toia, Bogdan; Pakzad, Mahreen; Hamid, Rizwan; Wood, Dan; Greenwell, Tamsin; Ockrim, Jeremy
Abstract: Objectives: To evaluate functional outcomes of surgery in patients with ectopic ureters diagnosed in adulthood; to review the world literature. Patients and methods: Patients were referred over 10 years. Data including surgical history, presenting symptoms, diagnostic modalities, interventions and functional outcomes were collected; and the world literature reviewed. Results: 9 women and 1 man had a mean age of 37 (range 20‐58). All women were referred with lifelong leakage. The man was referred with storage LUTS. Three women had heminephrectomy/nephrectomy with the distal ureter left in‐situ prior to referral. MRI was the predominant diagnostic tool but often took senior review to confirm the diagnosis. Excision of the ectopic ureter was performed with bladder neck reconstruction in 6 women, with concomitant rectus fascial sling in one patient. 4 of 6 (67%) women were cured of their stress incontinence with the bladder neck reconstruction alone, whilst two required further intervention. Three women had nephroureterectomy alone as primary treatment of which two were cured. The single male had heminephrectomy and excision of seminal vesicle. Conclusions: Ectopic ureter is a rare diagnosis in adults but should be considered in patients who describe lifelong incontinence. Fine slice MRI is the imaging of choice. Excision of the ureter with bladder neck reconstruction alone was successful in two‐thirds of patients, whilst further stress urinary incontinence surgery was required in one‐third. Malignancy in ureteric remnants is described in 8% of the world literature. Patients should be counselled of this risk if the ureter is left in‐situ.